PENGARUH GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) TERHADAP FAKTOR KESEHATAN MASYARAKAT PESISIR - Susilawati Susilawati; Fadya Safira Nasution (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The GERMAS program is a health development and improvement movement that aims to increase everyone's awareness and ability to live a healthy life in order to realize the highest degree of public health. One of the embodiments of the GERMAS program is that the Puskesmas as a primary health care facility conducts campaigns so that people can have awareness, willingness and ability to behave healthily to improve a better quality of life. Germas or the Healthy Living Community Movement is a movement launched to achieve SPM and PIS PK. So that it is in line with the aims of Germas. namely realizing a better degree of public health. The purpose of this study was to find out for a literature study how the Healthy Living Community Movement (GERMAS) influences the health factors of Coastal Communities. In conclusion, it is expected that people can implement the Germas program influenced by motivation from outside and within themselves, awareness of behavior and income in the family